Respuesta :

Answer:

The answer is r = 6a / (5m² - 1).

Step-by-step explanation:

The steps are :

[tex]m = \sqrt{ \frac{6a + r}{5r} } [/tex]

[tex] {m}^{2} = \frac{6a + r}{5r} [/tex]

[tex]5r {m}^{2} = 6a + r[/tex]

[tex]5r {m}^{2} - r = 6a[/tex]

[tex]r(5 {m}^{2} - 1) = 6a[/tex]

[tex]r = \frac{6a}{5 {m}^{2} - 1 } [/tex]

Answer:

r = [tex]\frac{6a}{5m^2-1}[/tex]

Step-by-step explanation:

Given

m = [tex]\sqrt{\frac{6a+r}{5r} }[/tex] ( square both sides )

m² = [tex]\frac{6a+r}{5r}[/tex] ( multiply both sides by 5r )

5rm² = 6a + r ( subtract r from both sides )

5rm² - r = 6a ← factor out r from each term on the left side

r(5m² - 1) = 6a ← divide both sides by (5m² - 1)

r = [tex]\frac{6a}{5m^2-1}[/tex]

ACCESS MORE